EKARISTI DI MEJA PERJAMUAN ESKATOLOGI | THE EUCHARIST AT THE ESCHATOLOGICAL TABLE - Ignasius Ledot (Institut Filsafat dan Teknologi Kreatif Ledalero, 2018)
Abstract This text critiques the concept of eucharist-eschatology which is found in two works by local NTT artists. Using an eschatological approach and a study of the document Sacrosanctum Concilium regarding liturgy, two important messages have been identified in those works. First, solidarity is an effort to share. This virtue is primarily seen in the attitude of God who left His/Her grandeur and took on the form of a human being. Second, the act of giving as a form of solidarity comes from an awareness of the missionary aspect of the vocation of the faithful. Via the artistic works of two local artists, the faithful are helped to consider and idealise the eschatological eucharist. These two works show the clear connection between the celebration of the eucharist in the world and the eternal eucharist, the place where humanity meets God who is both intimate but also majestic. Keywords: Church, Eucharist, Eschatology, Last Supper, Catechetics, Lord Abstrak Tulisan ini bertujuan untuk mengulas konsep ekaristi-eskatologi yang terdapat di dalam dua lukisan karya pelukis lokal NTT. Dengan menggunakan pendekatan eskatologi dan studi dokumen Sacrosanctum Concilium tentang liturgi ditemukan dua pesan penting dari dua lukisan tersebut. Pertama, solidaritas sebagai usaha untuk saling berbagi. Kebajikan ini pertama-tama tampak dalam sikap Allah yang memutuskan untuk meninggalkan keagungan-Nya dan mengambil rupa manusia. Kedua, aktus memberi sebagai bentuk solidaritas terlahir dari kesadaran akan aspek misioner dari panggilan umat beriman. Melalui karya lukis dua seniman lokal ini, umat dibantu untuk membayangkan dan mencita-citakan ekaristi eskatologi. Dua lukisan ini memperlihatkan hubungan yang jelas antara perayaan ekaristi di dunia dan ekaristi kekal, tempat manusia menjumpai Allah yang akrab sekaligus yang agung. Kata-kata Kunci: Gereja, Ekaristi, Eskatologi, Perjamuan Akhir, Katekese, Tuhan